Systematic study to evaluate anti-diabetic potential of Amaranthus spinosus on type-1 and type-2 diabetes - Bavarva, J. H.; Narasimhacharya, A. V. (Cellular and Molecular Biology, 2013)
The present study was designed to systematically investigate the antidiabetic potential of Amaranthus spinosus leaves which are traditionally known to have various medicinal properties and used for the treatment of diabetes mellitus. The ethanolic extract of leaves of Amaranthus spinosus was administered (150, 300 and 450mg/kg bw) to type-1 and type-2 diabetic rats. Standard drugs, glibenclamide and metformin were used as a positive control for comparison. Changes in carbohydrate and lipid metabolism and antioxidants were assessed and compared with control and standard drug treated animals. Among the standardized extract doses tested (150, 300 and 450 mg/kg bw), higher doses significantly decreased plasma glucose levels (p<0.01 and p<0.001), hepatic glucose-6-phophatase activity (p<0.01 and p<0.001) and increased the hepatic glycogen content (p<0.01) with a concurrent increase in hexokinase activity in both type 1 and 2 diabetic rats (p<0.01 and p<0.001). Besides, the higher doses also significantly lowered the plasma and hepatic lipids, urea, creatinine levels (p<0.001) and lipid peroxidation with an improvement in the antioxidant profiles (p<0.001) of both type-1 and type-2 diabetic rats. It is concluded that Amaranthus spinosus has potential antidiabetic activity and significantly improves disrupted metabolisms and antioxidant defense in type-1 and type-2 diabetic rats.